Factors Influencing Bursting Strength of Single Jersey Knitted Fabrics - Ariful Islam; Mohammad Billal Hossain; Emdadul Haq; Ahmed Saber Shravan; Arafat Rahman (European Scientific Journal, ESJ, 2022)
The purpose of this article is to assist engineers in making quick decisions to improve the strength of single jersey knit fabric. This article focused on the different parameters of the single jersey knit fabrics (like stitch length, yarn count, GSM, tightness factor, and fabric thickness) are considered to know their influence on the bursting strength. Five hypotheses have been developed for plain, pique, and fleece knits. Analyses of Variance (ANOVA), correlation coefficient, and regression analysis are executed using the STATA 14.1 program to test the hypotheses at a 5% level of significance. Three of the five hypotheses are rejected. This study supports that the bursting strength of the fabric is dependent on the tightness factor, stitch length, and count of the single jersey knitted fabrics. Here, the stitch length, count, and tightness factor are inversely proportional to the bursting strength. The GSM and fabric thickness have less impact on the bursting strength.